Transformation of business values in Russia and Iran: A comparative perspective - A S Blagova (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2016)
The article considers the transformations of business values in Russia and Iran defining the entrepreneurship as a driving force for both economic sphere and social life in general. The author believes that business values can be considered a practical example of the social perception of the state traditional axiological complex. Therefore, on the basis of statistical data of the international research center «GlobeScan», independent sociological Fund «Public Opinion», and analytical organization “Levada Center” the author studies the causes for the Russian society rejection of entrepreneurial values. The article presents the business values of the Islamic Republic of Iran in the comparative perspective focusing on the history of economic system reorganization in accordance with the principles of «tawhid economy» («economy of divine harmony») in order to reduce the vulnerability of the national economy under the globalization values and trends. The author analyzes business activities of Islamic funds («bonyad») as instruments of the state for promoting the necessary set of values, and explains the division of business according to the degree of European values acceptance depending on the affiliation with various political forces.